Hubungan Tingkat Depresi dengan Kualitas Hidup pada Masyarakat Daerah Bencana Pasca Gempa Bumi di Kabupaten Sleman Tahun 2008 - Nurhasanah Haripurnomo Kushadiwijaya, Carla Marchira (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: The problem of mental health in the community are complex and greatly varied and complex.They do not only include mental disorder but also numerous psychosocial problems, quality of life and harmony in life. Earthquake brings both physical damages and psychological trauma elationship if it goes far beyond coping capacity of the community that becomes the victim. The prevalence of mental disorder of the community that can survive is about 0.2% - 7.2% with major depression 6.4%. Quality of life of the community that suffers from major depression is lower than that of healthy people and those that have other mental disorder. Sub-district of Berbah, Kalasan and Prambanan feel the magnitude of earthquake and serious damages.Objective: To identify the relationship between level of depression and quality of life of the community at the disaster area post earthquake in the District for Sleman.Method: The study used cross sectional design. Subject of the study consisted of 721 people. Data were obtained through interview and observation. Instruments of medical outcomes Short Form 36 (SF-36) were used to measure quality of life and Beck Depression Inventory (BDI) were used to measure level of depression. Data were analyzed using bivariable and multivariable method with simple linear regression and multivariate linear regression.Result: The result of bivariable analysis showed that variables statistically had relationship with quality of life at District of Sleman were level of depression (r=0.561, R2=0.314), sex (r=0.042, R2=0.002), marital status (r=0.126; R2=0.016), income (r=0.092, R2=0.008) and social interaction (r=0.171, R2=0.029). The result of multivariable analysis showed that there were three variables statistically significant, i.e. level of depression, social interaction and sex (Adjusted R2=0.334).Conclusion: level of depression, social interaction and sex were risk factors of quality of life of the community post earthquake in the District of Sleman and they were statistically significant (p<0.05).Keywords: quality of life, level of depression, risk factors